Implementation of a New Architecture for the US National Accounts - Jorgenson, Dale W; Landefeld, J. Steven (American Economic Review, 2009)
The development of national accounts is one of the greatest innovations in economics. These accounts are the mainstay of macroeconomic analysis and economic policy and have been cited as one of the reasons for post-WWII stability in the United States and other developed economies. The national income and product accounts (NIPAs) in the United States and the national accounts of other countries were created in the aftermath of a major financial collapse and the Great Depression. However, they have focused on measuring growth and fluctuations in gross domestic product (GDP) or national income with limited linkages to financial flows and balance sheets. Despite the postwar explosion of theoretical, empirical, and policy work on the sources of economic growth, the national accounts have failed to develop integrated production accounts with inputs as well as outputs in current and constant prices. In addition, there has been little progress on linking national accounts to expanded measures of production. These would cover household production and the use of natural resources and the environment. Similarly, expanded measures of investment would cover R&D, intangibles, human capital, and other near-market goods and services. This paper presents a comprehensive and consistent macroeconomic framework, which we DATA WATCH: IMPLEMENTATION OF A NEW ARCHITECTURE FOR THE US NATIONAL ACCOUNTS